Impact of covid-19 on mood of dental professionals worldwide - Müberra Kulu; Filiz Özsoy; Esra Bihter Gürler (Konselor, 2022)
Oral health professionals perceive that dentistry is more stressful than other health professions. Supporting the mental health of dentists is a critical part of Covid-19 pandemic. The present study designed to investigate future anxiety and stress of dentists worldwide due to Covid-19 pandemic. A total of 1022 participants completed a self-administered online questionnaire. The relationships between variables are evaluated by Student’s unpaired t-tests and Mann-Whitney U test. Relationships with p<0.05 or less were considered statistically significant. The result of research is The mean ±SD  perceived stress scale was 34.17±5.32 females were insignificantly higher than males, whose mean was 33.13± 5.75. Similar to the perceived stress, the mean ±SD future anxiety was 111.3±32.97 in females and 98.99±33.35 in males. Future anxiety is not personal, it is societal and there is no significant difference between males and females in any subject.